Pengaruh Gaya Kepemimpinan, Motivasi Kerja, Dan Kepuasan Kerja Terhadap Kinerja Pegawai(Studi pada Pegawai RSUD dr. Soediran Mangun Sumarso Wonogiri) - Wardani, Nur Indah, Drs. Eko Sugiyanto, M.Si (2016)
Employee performance is an important factor in the company, because it can determine the success of the company. So that employees are expected to complete the task on time to achieve corporate objectives. This study aims to determine the effect of leadership style, employee motivation and job satisfaction to employee performance dr. Soediran Mangun Sumarso Wonogiri. Data collected through questionnaires and conducted on 50 employees at dr. Soediran Mangun Sumarso Wonogiri. Analysis of the data in this study using SPSS. The sampling technique used was purposive sampling. Methods of data analysis used in this research is multiple linear regression to test and prove the hypothesis of the study. The analysis showed that the positive effect of leadership style on employee performance. Work motivation positive effect on employee performance and job satisfaction has positive influence on employee performance.